Implementation Evaluation Based Learning Curriculum 2013 Implementation of Activity Based on Learning Tematik in Elementary Schools in Labuhanbatu District - Wan Sri Putri Saadah; Rahmad Husein; Siti Julaeha (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This research is a descriptive qualitative research which aims to describe the implementation of the 2013 Curriculum in the learning process in terms of learning planning, learning implementation, and learning evaluation. The population and sample in this study were teachers and students of Public Elementary Schools throughout Labuhanbatu Regency who have implemented the 2013 Curriculum since its inception in 2013, namely SD Negeri 28 Bilah Barat, SD Negeri 01 Bilah Barat, SD Negeri 08 Rantau Selatan, SD Negeri 11 Rantau Selatan, SD Negeri 15 Rantau Utara, and SD Negeri 06 Rantau Utara. The samples in this study were 46 for teacher respondents and 182 for student respondents at SD Negeri Labuhanbatu Regency. The instrument in this study was a semi-open questionnaire containing statement items, and the variable questionnaire was measured using a Likert scale. The results showed that the teacher's understanding of 2013 Curriculum-based learning planning was in the quite good category, with an average percentage of 74.72%. This is evidenced by the teacher's ability to compile a syllabus and lesson plans. The teacher's understanding of the implementation of curriculum-based learning in 2013 is in the good category, with an average percentage value of 76.13%. This can be seen from the teacher's ability in terms of class mastery. The teacher's understanding of the 2013 Curriculum-based learning evaluation is in the quite good category, with an average percentage of 73.5%. This can be proven by the teacher's ability to take an authentic approach. Meanwhile, the students' responses about the implementation of 2013 Curriculum-based learning carried out by the teacher showed a fairly good category, with an average percentage of 72.75%. For students' perceptions about the evaluation or assessment of learning based on the 2013 Curriculum conducted by the teacher, it is in the quite good category, with an average percentage of 73%.